2020
DOI: 10.1089/whr.2020.0082
|View full text |Cite
|
Sign up to set email alerts
|

Nonmydriatic Photographic Screening for Diabetic Retinopathy in Pregnant Patients with Pre-Existing Diabetes in a Safety Net Population: 1 Year Results from the Diabetic Retinopathy in Pregnant Patients Study

Abstract: Background: Pregnant patients with pre-existing diabetes mellitus (DM) are at increased risk for development or progression of existing diabetic retinopathy (DR). A quality improvement project was initiated to improve DR screening during pregnancy at a safety net hospital. This article highlights the utility and generalizability of our telemedicine-based screening model. Materials and Methods: In April 2018, we implemented a photographic retinal screening system in the Maternal Fetal Medicine (MFM) clinic at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(48 reference statements)
0
3
1
Order By: Relevance
“…The rate of DR screening in pregnancy over the four‐year study period was 16%. This compares poorly to only one other study in pregnancy that found a screening rate of 69% 4 . Furthermore, this rate is significantly below that of DR screening outside of pregnancy, which has been documented as ranging between 52% and 77% 12,13 …”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…The rate of DR screening in pregnancy over the four‐year study period was 16%. This compares poorly to only one other study in pregnancy that found a screening rate of 69% 4 . Furthermore, this rate is significantly below that of DR screening outside of pregnancy, which has been documented as ranging between 52% and 77% 12,13 …”
Section: Discussioncontrasting
confidence: 87%
“…This compares poorly to only one other study in pregnancy that found a screening rate of 69%. 4 Furthermore, this rate is significantly below that of DR screening outside of pregnancy, which has been documented as ranging between 52% and 77%. 12,13 Of those who had screening, six patients' (26%) screens noted DR, and of these, three patients (13%) screened had DMO.…”
Section: Rates Of Dr Screeningmentioning
confidence: 94%
See 2 more Smart Citations